DISCLOSURE ON INTELLECTUAL CAPITAL IN ANNUAL REPORTS OF NASDAQ OMX BALTIC-LISTED COMPANIES - Ramanauskaitė, Agnė; Laginauskaitė, Marija Rita (Ekonomika, 2015)
According to the current accounting standards, only a minor part of intellectual capital is presented in financial statements. Nevertheless, more and more companies in Lithuania and abroad reveal information about their intellectual capital in their annual statements. Therefore, the object of this paper is the disclosure of information on intellectual capital, and the aim is to reveal the trends of disclosure of information on intellectual capital based on annual reports by Nasdaq OMX Baltic-listed companies in the years 2010 to 2012. The main method applied in the present article is content analysis. Results. On the grounds of the described research methodology, the content analysis of annual reports dated from 2010 to 2012 by Nasdaq OMX Baltic-listed companies was performed. By applying the “QDA Miner” software, intellectual capital-related terms were calculated and distributed into three categories (human, relational, and organizational) in terms of the assets and liabilities. The obtained results of the three countries were compared in order to reveal the trends of development; furthermore, a correlation analysis was conducted to reveal the relationship between the market capitalization of a specific country and the level of disclosure on the intellectual capital of enterprises. Conclusions. The present research reveals that the total disclosed information on the intellectual capital of the Nasdaq OMX Baltic-listed companies was increasing each year from 2010 to 2012. On the other hand, the research shows that the trends and the structure of the disclosed information on the intellectual capital are different in each Baltic country. The highest amount of information was revealed by Lithuanian enterprises and the lowest amount is shared by Estonian enterprises. The best-covered information on the intellectual capital presents the employees as an asset while the most scantily revealed information describes intellectual liabilities.
Keywords: intellectual capital; disclosure; content analysis; Baltic states; annual reports